2014
DOI: 10.1590/bjpt-rbf.2014.0063
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between the climbing up and climbing down stairs domain scores on the FES-DMD, the score on the Vignos Scale, age and timed performance of functional activities in boys with Duchenne muscular dystrophy

Abstract: BACKGROUND: Knowing the potential for and limitations of information generated using different evaluation instruments favors the development of more accurate functional diagnoses and therapeutic decision-making. OBJECTIVE: To investigate the relationship between the number of compensatory movements when climbing up and going down stairs, age, functional classification and time taken to perform a tested activity (TA) of going up and down stairs in boys with Duchenne muscular dystrophy (DMD). METHOD: A bank of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 23 publications
1
5
0
3
Order By: Relevance
“…In the present study, in which patients with Vignos 1-3 (Vignos et al, 1963) participated, the timed performance of the DMD and control groups did not differ in the first assessment. However, timed performance can be longer (and less efficient) in patients with higher Vignos classifications, as observed in past studies (Fernandes et al, 2014;Martini et al, 2015) and in the present study (timed performance got longer as DMD progressed).…”
Section: Timed Performance Versus Compensatory Movementssupporting
confidence: 88%
See 2 more Smart Citations
“…In the present study, in which patients with Vignos 1-3 (Vignos et al, 1963) participated, the timed performance of the DMD and control groups did not differ in the first assessment. However, timed performance can be longer (and less efficient) in patients with higher Vignos classifications, as observed in past studies (Fernandes et al, 2014;Martini et al, 2015) and in the present study (timed performance got longer as DMD progressed).…”
Section: Timed Performance Versus Compensatory Movementssupporting
confidence: 88%
“…Both Carvalho et al (2015) and Martini et al (2015) found correlations between the number of compensatory movements and the timed performance on 10 -m walking. Fernandes et al (2014) found that timed performance correlated with the number of compensatory movements on climbing up and down steps. These studies show that for samples of ambulatory children with DMD with higher clinical variability (Vignos 1-6) timed performance and compensatory movements are correlated.…”
Section: Timed Performance Versus Compensatory Movementsmentioning
confidence: 96%
See 1 more Smart Citation
“…Adicionalmente, visto que o declínio das atividades motoras durante o curso da doença é inevitável, o uso de escalas de avaliação funcional se faz necessário para acompanhamento clínico e guia de condutas terapêuticas. Na prática clínica, a observação de atividades funcionais é um exame simples e acessível 25 30,[32][33][34][35]37 .…”
Section: Tipo 4 (Adulta)unclassified
“…Quanto maior a pontuação obtida, maior o comprometimento e a dependência funcional apresentada pelo paciente 25,39,40 46,47,48,49,50,51 .…”
Section: Escala De Vignos E Brooke (Evb)unclassified